A Review of Evidence Extraction Techniques in Big Data Environment - Mokhtar S.H.; Muruti G.; Ibrahim Z.-A.; Rahim F.A.; Kasim H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Big data; Computer crime; Digital forensics; Electronic crime countermeasures; Environmental regulations; Analytic method; Business Process; Computer engineers; Court of law; Evidence extraction; Information eras; New technologies; Tools and techniques; Data mining